RPA implementation in invoice factoring - Plyhm, Max (2021)
Robotic Process Automation (RPA) is an automation technology, which allows organizations to automate their high volume, simple and repetitive tasks. By implementing RPA, the organizations can refocus human resources into other value creating tasks and increase efficiency while limiting human error. The aim of this master’s thesis was to study the suitability of RPA in an invoice factoring process. The focus of this study was on the positive and negative aspects of a possible RPA implementation would bring to the organization, what a successful RPA project would look like and if RPA is the correct automation technology for the process. The case company in question is a medium sized financial services organization in Finland. In the literature review portion of this study the case for RPA implementation is built based on previous research on the subject. The literature review is divided into two parts. The first part looks at RPA in general and then expands to the strengths and weaknesses of RPA, the suitability of RPA and then finally what a possible implementation could look like. The second part focuses on how to conduct a successful RPA project. Based on the findings of this study, RPA is a suitable automation tool for part of the process. The part where simple data searches are being made to determine eligibility to finance are more than suited to be automated for RPA. The study also finds that RPA is best seen as a temporary solution to solve the simplest and most pressing automation issues organizations have, while developing more cognitive and capable technologies on the side. The organizational changes that a RPA implementation can be broad but were mainly seen as positive. This includes the change of job description, completely new positions and the change of organizational culture as a whole. The study revealed the success factors for a successful RPA project to being a robust communication, a well developed plan, organizational preparedness and proper documentations. The findings of this study partially confirm the findings of previous studies but the lack of specific studies into invoice factoring leaves room for further studies. This study can be used as a guide in the planning phase of a RPA implementation project.